Aggregation Behavior of Some Asymmetric Porphyrins versus Basic Biological Tests Response. (20th October 2015) - Socoteanu, Radu; Anastasescu, Mihai; Oliveira, Anabela; Dobrescu, Gianina; Boscencu, Rica; Constantin, Carolina
Abstract : Fractal analysis of free bases porphyrins was computed on atomic force microscopy (AFM) micrographs using two different methods: the correlation function method and the variable length scale method. The correlation function method provides fractal dimension only for short scale range; results indicate that only few images have fractal properties for short ranges; for the rest of them, no fractal dimension was found using the correlation function method. The variable length scale method occur information for long range scaling. All samples have fractal properties at higher scaling range. For three samples the correlation function method leads to the same fractal dimension as the variable length scale method and scaling ranges for both methods overlap. Results show the necessity to use both methods to describe the fractal properties of AB3    meso -porphyrins that may be used to predict their relative cell localization. In order to emphasize the influence of fractal and textural properties the results regarding their self-similarity and texture/morphology were further compared with their behavior in biological assessment, that is, functionality of some Jurkat cell lines.